Analisis Industri pada Ritel Convenience Store: Kasus 7-Eleven (Sevel) - Son Wandrial; Enggal Sriwardiningsih (Binus Business Review, 2013)
7-Eleven, a Japanese retailer is very popular and loved in Jakarta. 7-Eleven or commonly abbreviated to Sevel is now reaping a lot of fans because of the concept of 7-Eleven Indonesia, found only in Indonesia. With the rising middle classes in Indonesia, 7-Eleven becomes a luxurious place for hanging-out but affordable. Consequently, it is attracting the interest of investors to make such a kind of convenience store like Sevel, and it is likely the competition in this sector will be increasingly fierce. PT. Modern’s initial plans are to focus onopening stores in Jakarta, targeting densely-populated commercial and office areas, to offer Indonesian workersa convenient place to shop for lunch, snacks, and emergency items. The company’s goal is to focus on opening stores in Jakarta in its first years of operation. Other major cities, such as Bandung, Semarang, and Surabaya offer for future expansion opportunities. The objective of this article is to describe the competitive condition in convenience store industries using Porter’s Five Forces model. Although the competition is fierce andunfavorable industry condition, Sevel is still leading and dominating the convenience store market in Indonesia.